Biodegradation of modified Poly(lactic acid) based biocomposite films under thermophilic composting conditions. (July 2019) - Kalita, Naba Kumar; Nagar, Mukesh Kumar; Mudenur, Chethana; Kalamdhad, Ajay; Katiyar, Vimal
Abstract: This study evaluates the aerobic biodegradation of modified Poly(lactic acid) (PLA) based biocomposites under composting condition. Samples of neat PLA (NPLA), PLA/chitosan 5% (modified) (PLA/Chitosan), PLA/CNCSO4 (̴1%) (PLA/CNC) and PLA/Gum Arabic 5% (modified) (PLA/Gum) were used for evaluation of biodegradation under simulated composting condition without adding any inoculum to the compost and utilizing the thermophilic microflora already present in the compost. Various analytical techniques like molecular weight analysis, differential scanning calorimetry (DSC), contact angle analysis and microbial colony count were used for analysis of biodegradation. Colony formation was analyzed and was found to be 5.12 × 10 6 cfu/ml in PLA/Chitosan sample. Contact angle measurement was employed for understanding biodegradation over a period of 70 days for the biocomposites. Biodegradation study was also confirmed through decrease in transparency and major peak shift in infra-red (IR) spectroscopy. DSC studies showed increase in crystallinity for all the degraded test samples, which confirms biodegradation. The results confirmed modified PLA films as biodegradable and also confirmed suitability of the test system for studying biopolymer biodegradation. Highlights: This study showed the biodegradation of PLA based biocomposites. Thermophilic composting condition implemented in biodegradation study. Contact angle analysis provided insights of PLA biodegradation. Aerobic composting at 58 °C (±5) was used for understanding biopolymer based film biodegradation. Results obtained validated our biodegradation test system.